A first principles study of CO2 adsorption on α-SiO2(001) surfaces1. Issue 31 (21st August 2015) - Malyi, Oleksandr I.; Thiyam, Priyadarshini; Boström, Mathias; Persson, Clas
<x xml:space="preserve">Abstract</x> CO2 interaction with cleaved and reconstructed α-SiO2(001) surfaces is studied using first principles calculations.